1980
DOI: 10.1016/s0022-5347(17)55268-4
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Renal Venous System and Unexplained Renal Hematuria

Abstract: Since 1968, 152 patients with unexplained renal hematuria have been treated at our clinic. Renal angiography in 46 patients who did not respond to conservative therapy revealed 21 abnormalities of the vascular system. Of these 21 patients 10 had or were suspected to have renal pelvic and ureteral varices, and 8 had congenital anomalies of either the inferior vean cava or the renal vein. Therefore, it was confirmed that vascular abnormalities were associated with the unexplained renal hematuria in these cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 11 publications
1
22
0
3
Order By: Relevance
“…[48][49][50] It varies from microhematuria to macrohematuria, occasionally with resultant anemia that requires blood transfusions. 3,[50][51][52][53][54][55] Cystoscopy may identify a left ureteral origin. 22,24,50,56,57 In a study by Shin et al, 30 the causes of isolated hematuria could not be identified by routine methods in 69% of pediatric cases.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…[48][49][50] It varies from microhematuria to macrohematuria, occasionally with resultant anemia that requires blood transfusions. 3,[50][51][52][53][54][55] Cystoscopy may identify a left ureteral origin. 22,24,50,56,57 In a study by Shin et al, 30 the causes of isolated hematuria could not be identified by routine methods in 69% of pediatric cases.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Mitty and Goldman [ 15] report this finding in 2 children aged 5 and 6 years, Hayaski et al [16] in a child of 10 years, but Di Lanoet al [14] did not find it in patients below the age of 14 years. Ingelfinger et al [2] in their review of 128 children with gross hematuria did not report any patients with this problem.…”
Section: Discussionmentioning
confidence: 93%
“…Both lead an active lifestyle with no limitations. The decision to follow these patients conservatively seems appropriate, since the well-being of patients appears no different than those subjected to sur gical excision or vascular reconstruction [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Only few cases showing clinical symptoms with this anomaly have been reported in the literature [8,13,14,17,26]. Satyapal et al [21] reported no symptomatic patients, proclaiming that all renal vein variations are clinically silent and remain unnoticed until discovered during venography, operation or autopsy.…”
Section: Discussionmentioning
confidence: 99%